2011
DOI: 10.2460/ajvr.72.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contribution of gyrA mutation and efflux pumps to fluoroquinolone and multidrug resistance in pathogenic Escherichia coli isolates from dogs and cats

Abstract: ResumenSe estudió la disposición plasmática y urinaria de marbofloxacina en caninos (n = 6) tras la aplicación intramuscular de 2 mg/kg. En distintos tiempos posadministración se tomaron muestras de sangre hasta las 24 h, y de orina solo en los caninos machos (n = 4) a las 4, 8, 12 y 24 h. Se realizó una extracción líquido-líquido del analito con agua, metanol y centrifugado a 13.500 r. p. m. a 4 °C. La separación y cuantificación se realizó por HPLC mediante la elusión isocrática en fase reversa, utilizando c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…11 Previous studies have shown that the primary target of FQ in E. coli is DNA gyrase and mutations in the gyrase genes can lead to development of decreased susceptibility to FQs, thus complicating the treatment of infections. 4,5 Typically, a mutation in gyrA leading to the Ser-83 Leu substitution is the first gyrA mutation observed, which leads to a reduction in susceptibility; however, high-level FQ resistance (ciprofloxacin MIC . 4 mg/L) requires an additional mutation in gyrA at position 87 and at least one parC mutation at either position 80 or 84.…”
Section: Jac Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Previous studies have shown that the primary target of FQ in E. coli is DNA gyrase and mutations in the gyrase genes can lead to development of decreased susceptibility to FQs, thus complicating the treatment of infections. 4,5 Typically, a mutation in gyrA leading to the Ser-83 Leu substitution is the first gyrA mutation observed, which leads to a reduction in susceptibility; however, high-level FQ resistance (ciprofloxacin MIC . 4 mg/L) requires an additional mutation in gyrA at position 87 and at least one parC mutation at either position 80 or 84.…”
Section: Jac Discussionmentioning
confidence: 99%
“…Treatment can be further complicated when FQ-resistant E. coli isolates exhibit multidrug resistance phenotypes. 2,4 Resistance to quinolones is primarily attributed to chromosomal mutations in DNA gyrase and/or topoisomerase IV genes or mutations in the regulatory genes of the acrAB efflux pump. 5,6 Changes in cell membrane permeability and overexpression of the multidrug efflux pump are complementary mechanisms that contribute to high-level FQ resistance in clinical isolates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In E coli isolates, the inhibition of the efflux pump gene expression decreased the MIC of fluoroquinolone. [ 38 ] Furthermore, in this study, there were significantly more SNVs of Hp0970 (hefE) and Hp1329 (hefI) in the lower-level LVX-resistant clone than those in the higher-level LVX-resistant clones. In other words, a large number of SNVs may increase the risk of gene inactivation or activation.…”
Section: Discussionmentioning
confidence: 57%
“…Estas concentraciones muy superiores establecidas en experiencias realizadas con idénticas dosis por aplicación oral (16) serían suficientes para el tratamiento de infecciones urinarias no complicadas, por cuanto el éxito terapéutico depende de la dosis, el intervalo de aplicación, las concentraciones conseguidas (al menos cuatro veces la CMI), y que los microorganismos patógenos sean moderadamente susceptibles (26). Sin embargo, estos resultados son insuficientes para recomendar su aplicación a la dosis y por la vía ensayada, considerando la elevada manifestación de resistencia exhibida frente a las fluoroquinolonas (7,27), posiblemente por los valores de pH entre 5,5 y 7 dieta dependiente, de la orina de caninos (28), siendo menos eficaces las fluoroquinolonas en medio ácido (17,29,30). Por otro lado, la orina puede contener cantidades de magnesio, que reduce la actividad de las fluoroquinolonas, independientemente del pH (17,31).…”
Section: Discussionunclassified